2010
DOI: 10.1021/ac101222x
|View full text |Cite
|
Sign up to set email alerts
|

Size-Selective Microcavity Array for Rapid and Efficient Detection of Circulating Tumor Cells

Abstract: Circulating tumor cells (CTCs) are tumor cells circulating in the peripheral blood of patients with metastatic cancer. Detection of CTCs has clinical significance in cancer therapy because it would enable earlier diagnosis of metastasis. In this research, a microfluidic device equipped with a size-selective microcavity array for highly efficient and rapid detection of tumor cells from whole blood was developed. The microcavity array can specifically separate tumor cells from whole blood on the basis of differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
329
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 315 publications
(341 citation statements)
references
References 32 publications
5
329
0
1
Order By: Relevance
“…Furthermore, the randomly distributed holes are prone to significant coalescence of two or more holes allowing tumor cells to escape from the filter. More recent studies have shown that a variety of microfabrication techniques could be used to manufacture filters of different hole-types and densities [36][37][38][39][40][41][42][43][44][45] , but none of them were able to meet the critical requirements for both clinical application and fundamental studies. …”
mentioning
confidence: 99%
“…Furthermore, the randomly distributed holes are prone to significant coalescence of two or more holes allowing tumor cells to escape from the filter. More recent studies have shown that a variety of microfabrication techniques could be used to manufacture filters of different hole-types and densities [36][37][38][39][40][41][42][43][44][45] , but none of them were able to meet the critical requirements for both clinical application and fundamental studies. …”
mentioning
confidence: 99%
“…These authors successfully achieved a significant correlation between the numbers of CACs and the presence of cancer. In order to improve efficient detection of tumor cells from peripheral blood of patients with cancer, Hosokawa et al [99] have developed a microfluidic device equipped with a size-selective microcavity array which can specifically separate tumor cells from in the bloodstream on the basis of differences in the size and deformability between tumor and hematologic cells. The cells recovered on the microcavity array were further processed for image-based immunophenotypic analysis using a fluorescence microscope.…”
Section: Circulating Dna Versus Circulating Tumor Cells Techniquementioning
confidence: 99%
“…Some representative examples are exhibited here. Reproduced with permission 59. Copyright 2010, American Chemical Society.…”
Section: Introductionmentioning
confidence: 99%